2020
DOI: 10.1111/hsc.13161
|View full text |Cite
|
Sign up to set email alerts
|

Dementia care‐giving from a family network perspective in Germany: A typology

Abstract: Sustaining informal care-giving for people living with dementia (PWD) is a common objective of societies worldwide. Families can contribute substantially to the support of care-giving relatives. However, a deeper understanding of the impact of informal care-giving for PWD on family life is needed. Interviewing of multiple family network members-in addition to the primary carer-provides more insight into familial contexts of care-giving. This pilot study aims to explore how informal carers reconcile dementia ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Being able to preserve boundaries and to keep the influence of care on their personal lives at a low level depends on several conditions. Some of the carers have an advantaged care network which is characterised by, for example, a harmonious relationship between the network members who share care tasks or by having special expertise regarding the administration of care (Neubert et al, 2020a, 2020b). Moreover, the cared-for person’s preferences, character traits and extent of dementia support the reconciliation of informal care and personal life. All three of us, well I found that conversations or visits for more than half an hour are no longer possible.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Being able to preserve boundaries and to keep the influence of care on their personal lives at a low level depends on several conditions. Some of the carers have an advantaged care network which is characterised by, for example, a harmonious relationship between the network members who share care tasks or by having special expertise regarding the administration of care (Neubert et al, 2020a, 2020b). Moreover, the cared-for person’s preferences, character traits and extent of dementia support the reconciliation of informal care and personal life. All three of us, well I found that conversations or visits for more than half an hour are no longer possible.…”
Section: Resultsmentioning
confidence: 99%
“…In this type, which is made up of two adult-child primary carers, the negotiation is focussed on the emotional processing of the crisis. Factors that contribute to the imbalance between personal needs and care demands and influence the negotiation between them are a conflict-loaded relationship to other family members and the unshared or unequally shared distribution of responsibilities between family members (Neubert et al, 2020b). The carers are oriented towards the need for (psychological) help and self-reflection to, for example, understand the nature of dementia and the reasons for their overload. Then you can’t really; I’ll say it like this, above all if you don’t reflect and process, so that means ((breath)) such care also needs a stable person, I think; and if not then you break down with such care, […] I absolutely and totally urgently need more sessions [psychotherapy] because there is so much I want to get off my chest and want to understand why are they all leaving ?…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…accompanying care recipients, looking after them, helping with the household, and the like). The German typology created recently (Neubert et al, 2020) reflects the ways in which care is divided among family members caring for people with dementia -the families' approaches form an imaginary scale running from "we stick together" to "there's no other possibility". However, these typologies do not take into account the carers' experiences and feelings and their self-reflection -which is the focus of other, qualitative research (e.g.…”
Section: Kontakt / Journal Of Nursing and Social Sciences Related To Health And Illness S O C I A L S C I E N C E S I N H E A Lt Hmentioning
confidence: 99%